Bi-Phasic Dissonance in some Pinoy Boys’ Love Series - Devilles, Gary C (Archīum Ateneo, 2022)
The growing fascination with Pinoy Boy’s Love (BL) series, such as Gameboys, Hello Stranger, and Quaranthings can be construed as part of the long struggle of LGBTQI community for more inclusivity as most of its fans were also fans of Thai Boy’s Love series called “lakhon,” according to scholar Thomas Baudinette who studied that Pinoy fan sites actively appropriate or “creatively misread” these series. My paper now would like to follow up on the efficacy of these reparative readings in Pinoy BL series, if the creative misreading in Thai BL series can be carried over to their Pinoy BL counterparts, and how such readings fare with the culture of “machismo” or toxic masculinity that perpetuates in Philippine society. My approach will focus more on a closed reading of selected Pinoy BLs, namely, Gameboys, Hello Stranger, and Quaranthings and prove that in as much as these BL series offer safe space or creative appropriations for LGBTQI communities, they are also enablers of the status quo of homophobia, heteronormativity, and toxic masculinity. I argue that the same mechanism behind this fascination can be attributed to what Theodor Adorno would call the bi-phasic dissonance between general attitudes of homophobia and specific behaviors of heteronormativity, which reinforces an atmosphere of social contentment and ultimately avoids more critical and solemn speculation about the state’s role in our dire situation, in this pandemic.